Serological tests for primary biliary cholangitis - Aralica, Merica (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Diagnostic test accuracy). The objectives are as follows: To determine and compare the diagnostic accuracy in terms of sensitivity and specificity of different serological markers for diagnosis of primary biliary cholangitis in people suspected of having the disease. To investigate variation in the diagnostic accuracy of AMA, ANA, anti‐M2, anti‐sp100, anti‐gp210, anti‐PML, anti‐sp140, and anti‐EPO antibodies according to the following potential sources of heterogeneity. 1. Studies at low risk of bias versus studies with unclear or high risk of bias (as assessed by the Quality Assessment of Diagnostic Accuracy Studies (QUADAS‐2) tool) (Table 1). 2. Full‐text publications versus abstracts (this may indicate publication bias if there is an association between the results of the study and the study reaching full publication) (Eloubeidi 2001). 3. Prospective versus retrospective studies. 4. The prevalence of people who are symptomatic versus people who are asymptomatic (the presence of symptoms may increase the pretest probability). People who are symptomatic will be defined as people with fatigue (lasting more than three months; anaemia and hypothyroidism excluded), pruritus, jaundice, and abdominal pain in the absence of biliary stones, oesophageal varices, ascites, and liver failure (Prince 2004; AASLD 2009). 5. Studies that included 30% or less of participants with other autoimmune diseases versus studies that included more than 30% of such participants. 6. Detection of index tests by different types of immunoassays. 7. Diagnostic accuracy of anti‐M2, ANA, anti‐sp100, anti‐gp210, anti‐PML, anti‐sp140, and anti‐EPO according to the prevalence of AMA‐negative participants in the included studies. 8. Diagnostic accuracy of AMA, anti‐M2, ANA, anti‐sp100, anti‐gp210, anti‐PML, anti‐sp140, and anti‐EPO in participants suspected of primary biliary cholangitis referred from a general practitioner clinicversus people referred from specialist clinic. 9. Diagnostic accuracy of AMA, anti‐M2, ANA, anti‐sp100, anti‐gp210, anti‐PML, anti‐sp140, and anti‐EPO in participants without liver cirrhosis versus participants with liver cirrhosis (as defined by individual studies).